Bitcoin, the Blockchain, and Their Potential to Change Our World - Lantz, Lorne (O'Reilly Media, Inc., 2015)
Bitcoin is more than just a volatile currency. It also has the potential to replace credit cards, lower remittance rates, and empower the unbanked. And it's already forcing governments to pay attention. There's plenty of misinformation about bitcoin-people making money, hackers stealing money, people using it to buy drugs-so even if you're in the bitcoin space you likely don't know what it really is, and what value bitcoin and the blockchain technology can bring to the world. This video will help you gain the skills and language necessary to use bitcoin and explain it to others. This is your first step in understanding how bitcoin gives us an opportunity to rewrite the financial system, and how the blockchain has the potential to decentralize our world. This video will answer these and other burning questions: What is bitcoin and what is the blockchain? How can bitcoin potentially bring value to me? What are bitcoin miners? How can I store, send, and receive bitcoin? What are the fees to use bitcoin? Is bitcoin anonymous? How do I use a bitcoin ATM? How does the price of bitcoin get set? Should I accept bitcoin as payment? How can I secure my bitcoin? Is bitcoin legal in the US? What are all these alternative currencies? What does the future hold for bitcoin? This video also includes interviews with influential people in this nascent industry, including Andreas Antonopoulos, Greg Kidd, and a number of bitcoin miners. Lorne Lantz, a passionate bitcoin entrepreneur and educator, has built multiple financial technology startups. He's been programming for 20 years, and has deep domain knowledge in banking, payments and bitcoin. Lorne has launched several bitcoin projects and is currently building a more convenient method to remit money to the Philippines.